Energy efficient LEACH-C protocol for wireless sensor network - Tripathi, M; Gaur, M.S; Laxmi, V; Battula, R.B (Proceedings of third International Conference on Computational Intelligence and Information Technology, 2013)
To prolong the overall lifetime of the network, development of energy efficient routing protocol is a major issue in Wireless Sensor Network. Clustering Protocols are one of the approaches to serve this purpose. LEACH-C is a cluster based protocol in which cluster heads are selected by the base station randomly. All the nodes having the energy above average are eligible to be cluster heads. Base station runs a simulated annealing algorithm to find the optimal solution with better positions to reduce the energy consumption of cluster heads. This paper presents an Energy Efficient LEACH-C (EELEACH-C) protocol, in which base station runs a sorting algorithm to obtain a list of candidate cluster head nodes sorted in descending value their residual energy. After examining the candidate cluster head nodes it selects those with maximum residual energy and than calculate the quadratic sum of the distances from each cluster heads to its member nodes to find the optimal solution. Experimental result attests that the proposed protocol improves network longevity.